SMART RETAIL EVOLUTION: INTEGRATION OF AUGMENTED REALITY AND ARTIFICIAL INTELLIGENCE FOR ENHANCED CONSUMER SHOPPING EXPERIENCE WITH BIOMETRIC SECURITY - Sukumar Murali (INTERNATIONAL JOURNAL OF RESEARCH IN COMPUTER APPLICATIONS AND INFORMATION TECHNOLOGY (IJRCAIT), 2025)
This article presents an innovative approach to retail shopping through the integration of Augmented Reality (AR) and Artificial Intelligence (AI) technologies, enhanced with biometric security measures. The article addresses critical challenges in contemporary retail environments, including time constraints, health consciousness, and price comparison inefficiencies. The article combines cutting-edge AR hardware with sophisticated AI modules to create an intuitive shopping experience. Through a comprehensive analysis of core functionalities, security frameworks, and user experience design, the article demonstrates how this integration can transform traditional retail interactions. The article incorporates advanced features such as real-time product recognition, personalized shopping assistance, and secure blockchain-based transactions. The article emphasizes accessibility and user-centric design while maintaining robust security protocols. By leveraging edge computing, cloud infrastructure, and multi-modal interaction methods, the system offers a scalable and future-proof solution for evolving retail environments. This article contributes to the field by providing a detailed blueprint for next-generation retail systems that enhance consumer shopping experiences while addressing critical security and integration challenges.